The Smart PR Book A Practical Guide to the Art and Craft of Public Relations - Stahl, Sandra (LID Publishing, 2025)
This is a concise and practical manual for understanding and implementing public relations campaigns and communications in today's business world. Modern-day PR is both science and an art, strategy and execution, fact and finely tuned intuition. This book, written by a leading PR practitioner and educator, enables you to create the right mindset and build the necessary skills to meet the communications challenges that face most businesses. This includes mastery of the fundamentals of PR, cultivating unbridled curiosity and creativity, the art of listening, and never losing sight of the business objectives at hand
Description based on publisher supplied metadata and other sources